(untitled) (Heteroglossia – studia kulturoznawczo-filologiczne, 2022)
The aim of the paper is to analyse the evidential meanings encoded by selected Polish verbs of perception. Evidentiality is a category whose primary function is to mark the speaker’s source of information on which his/her claim is based; this may be direct observation/experience, inference from observable data, general knowledge, someone’s report, or other types of evidence. Cross-linguistically, the category of evidentiality may be defined narrowly as marking of the information source only by strictly grammatical means; alternatively, evidentiality may be understood broadly as marking of the information source plus additional epistemic values, and this can be done through grammatical and/or lexical means. The present paper adopts the latter understanding of evidentiality; within this broadened view, evidential strategies can be discussed more holistically. Perception verbs in Polish may be divided into different subgroups; from the evidential perspective, the division into object-oriented and subject-oriented verbs provides the most significant contrast to consider the problem of which forms of perception verbs encode evidential meanings. The next problem to be addressed is which evidential values are encoded by these forms. It is usually the speaker’s direct perceptual experience that is indicated by perception verbs; however, certain forms may encode indirect information sources, such as inference or someone’s report.